(untitled) (Global Journal of Medical Research, 2024)
The persistence of postoperative nausea and vomiting (PONV) episodes can cause further complications to the patient, such as: dehiscence of the surgical wound, dehydration, esophageal rupture, hematoma, hemorrhage, and may even lead to death. Considering its high incidence in surgical procedures of the face and oral cavity, the present study aimed to evaluate the incidence of PONV episodes in oral and maxillofacial surgeries under general anesthesia as well as to identify the main risk factors associated with these episodes. This analytical, observational, retrospective study was based on the documentary analysis of 200 medical records of patients who underwent oral and maxillofacial surgery at the Walter Cantídio University Hospital of the Federal University of Ceará.